Preliminary study on chemical and physical changes during the smoking process of tangigue (Scomberomorus Commersonii). - Narida, Mae Margarita B. (College of Fisheries, University of the Philippines, 1985)
Changes in the chemical, microbiological and physicalproperties of tangigue (scombermorus commersonii) during smoking using five different time0temperature combinations were assessed. These was moisrure reduction of 6.8-9.5% from the raw material to the final product/ this low moisture loss resulted in juicy smoked products. K-valuye reached 49-68% after 5 to 8 hours smoking from the initial 14-22%. This value means spoiled for wet fish but in smoked tangigue, the product was still fresh and acceptable. Denaturation of protein was rapid during the salting step and high temperature (83 degree C) smoking or hot-smoking. The rate of increase in percentage denaturation of actomyosin (%DAM) was 9%/hr and 12/hr during salting and 9% hr during smoking at 83 degree C. this was faster than the rate in 35 degree C and 40 degree C smoking which were 0.75%/ hr and 3.25%/hr, respectively. There was slow but continuous oxidation of lipids in the product where raw material had been processed immediately upon receipt. On the other hand, the anti-oxidization of fish lipids where raw material had undergone overnight freezing. Histamine formation was rapid at smoking temperature of 35 degree C while at temperature above 40 degree C, histamine formation was slowed down. There was an increase of 10.84 ppm histamine from the raw material to the final product at 35 degree C smoking. On the other hand, smoking at 40 degree c and above caused increased of 0.66 ppm to 3.72 ppm. Microbiological analyses had shown that smoking at 45 degree C and higher affected 96-99% reduction in the microbiological load f the product. Furthermore, anaerobic spore formers which are of public health significance such as clostridium botulinum and clostridium perfringens were not natural microflora of the raw materials. Sensory characteristics of the fish changed from the initial pinkish to white translucent firm flesh to the white, opaque and slightly stiff brined fillet and finally to the soft and juicy golden-brown product.product. Furthermore, the tasks panel agreed on the acceptability of the salt and smoke of flavour of the product but had differences in the assessment of texture. This however, is beyond the scope of this study.